Lompat ke konten Lompat ke sidebar Lompat ke footer

Advertisement

Diketahui f(x) = 2x + 1, g(x) = 5 – 3x , h(x) = x2 – 1 Tentukan:

Diketahui f(x) = 2x + 1, g(x) = 5 – 3x , h(x) = x2– 1

Tentukan:

A. (fogoh) (x) =

B. (fog) (-2) =

C. (gofoh) (3) =

Jawab:

A. (goh)(x) = 5 – 3(x2– 1)= 8 – 3x2

    (fogoh) (x) = 2(8 – 3x2) + 1

    (fogoh) (x) = 17 – 6x2

B. (fog)(x) = 2(5 – 3x)+ 1

                = 11 – 6x

    (fog)(-2) = 11 – 6(-2) = 23

C. (foh)(x) = 2(x2– 1) + 1 = 2x2– 1

    (gofoh)(x) = 5 – 3(2x2– 1)

    (gofoh)(x) = 8 – 6x2

    (gofoh)(3) = 8 – 6(32) = 8 – 54 = -46